From shared climate to personal ecosystems: Why some people create unique environments. (November 2021) - Friedman, Ray; Olekalns, Mara
Much of organizational behavior research looks at how social context influences individuals' experiences and behaviors. We add to this view by arguing that some individuals create their own contexts, and do so in a way that follows them across dyads, groups, and organizations. We call these individual-specific contexts "personal ecosystems, " and propose that they are created when an actor consistently engages in visible behaviors that trigger similar and visible reactions across targets of that behavior. We attribute the formation of personal ecosystems to social inertia, and identify three individual traits that increase the likelihood that an individual's behavior is consistent across people and situations: low self-monitoring, implicit beliefs, and low levels of emotional intelligence. Finally, we discuss why understanding personal ecosystems is important for organizations, identify managerial implications of this phenomenon, and strategies for diminishing the likelihood of having personal ecosystems.